disruptive behavior and Cognitive Failure for Preparatory stage students - الزهيري, محسن صالح حسن (Al-Adab Journal, 2019)
the research objectives are conducted to the following :1- To know the level of disruptive behavior for Preparatory stage students 2- To know the level of Cognitive Failure for Preparatory stage students 3-To know the relationship between the disruptive behavior and Cognitive Failure for Preparatory stage students The current research has determined sample of Preparatory forth stage students (scientific and literary) for both males and females in Baghdad (morning studies) for 2014-2015. Theoretical frameThis research viewed several adoptes in The research procedures results Building Adopting disruptive behavior scale 1-(Suhail 2007) and Adopting Cognitive Failure scale(AL - Kipiy) after assures its truthes and stability on its articles -2-The two mentioned measures were applied at the same time on sample educational counselors (200) students male and female students during 24 - 29/3/2015 .the researcher used the following . Data had been analyzed with help of statistic programs for social sciences in data process(SPSS)As a result, it had been reached to results listed below 1- The research results showed that the Preparatory stage students not adopted disruptive behavior 2-results showed that the Preparatory stage students endowed with Cognitive Failure 3-Results showed that there is nigtive connection relationship between for Preparatory stage male and female students disruptive behavior and Cognitive Failure The researcher submitted some recommendations andsuggestions